2016
DOI: 10.4137/cmc.s32667
|View full text |Cite
|
Sign up to set email alerts
|

CETP Inhibition: Past Failures and Future Hopes

Abstract: The atheroprotective role of high-density lipoprotein cholesterol (HDL-C) in cardiovascular disease has been unequivocally established, and epidemiological data have clearly demonstrated a strong inverse relationship between HDL-C levels and the risk of cardiovascular events, which is independent of the low-density lipoprotein cholesterol (LDL-C) levels. Thus, it would be logical to hypothesize that raising HDL-C might potentially lead to a reduction of cardiovascular risk. Cholesteryl ester transfer protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 55 publications
2
33
0
2
Order By: Relevance
“…This relationship has withstood repeated evaluation in large scale population studies; however, there is a great deal of uncertainty about the nature of this relationship and whether HDL is “good” because it is directly protective against CVD or if the cholesterol content of HDL (HDL-C) is simply a biomarker of some other protective process, and in fact, has no direct causal relationship with CVD (2). While there is a great deal of functional data and some clinical data to support the hypothesis that HDL is playing a direct protective role against CVD, several recent studies indicate that pharmacological manipulation (3) or naturally occurring genetic mutations (4), which result in increased HDL-C, do not translate to a reduced risk of cardiovascular events. Many view these studies as a significant blow to the HDL field, suggesting a lack of importance of HDL in CVD; however, there is an alternative interpretation of these results.…”
Section: Our Current Understanding Of Hdl Functionmentioning
confidence: 99%
“…This relationship has withstood repeated evaluation in large scale population studies; however, there is a great deal of uncertainty about the nature of this relationship and whether HDL is “good” because it is directly protective against CVD or if the cholesterol content of HDL (HDL-C) is simply a biomarker of some other protective process, and in fact, has no direct causal relationship with CVD (2). While there is a great deal of functional data and some clinical data to support the hypothesis that HDL is playing a direct protective role against CVD, several recent studies indicate that pharmacological manipulation (3) or naturally occurring genetic mutations (4), which result in increased HDL-C, do not translate to a reduced risk of cardiovascular events. Many view these studies as a significant blow to the HDL field, suggesting a lack of importance of HDL in CVD; however, there is an alternative interpretation of these results.…”
Section: Our Current Understanding Of Hdl Functionmentioning
confidence: 99%
“…32, 33 Failure of CETP inhibitors to reduce cardiovascular events has indicated that it is not sufficient to simply raise HDL cholesterol. 34 The functional capacity of HDL in RCT might be more important mechanistically. Increased fecal cholesterol excretion is a prominent mechanism of action of phytosterols in foods and supplements, 35 but there have been no interventional studies with CVD outcomes to firmly establish the treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis assumes that statin-mediated risk reduction is effective immediately upon the initiation of statin therapy, and that the level of treatment adherence over the course of the VOYAGER studies (typically 4–6 weeks) would be continued over a 10-year period [19]. …”
Section: Discussionmentioning
confidence: 99%